2015
DOI: 10.3899/jrheum.150607
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Care in Gout: From Prescriber to Patient

Abstract: Patients and GP wished to know more about gout and its management. Greater success in establishing and maintaining ULT will require further and better education to substantially benefit patients. Also, given the prevalence, and personal and societal significance of gout, innovative approaches to transforming the management of this eminently treatable disease are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 24 publications
4
83
0
3
Order By: Relevance
“…Healthy.me Gout is a modified version of Healthy.me, a general health app that has been shown to improve influenza vaccination rates and address the needs of breast cancer survivors [17][18][19]. Healthy.me Gout was developed after interviews with patients regarding their current gout management [20], a review of commercially available apps for patient selfmanagement of gout [15], and subsequent feedback from gout patients of these apps and the generic version of Healthy.me [21]. Healthy.me Gout contained six features depicted in Figure 4 and summarised in Table 1.…”
Section: Study 2: Pilot Testing Of the Gout Self-management Mobile Apmentioning
confidence: 99%
“…Healthy.me Gout is a modified version of Healthy.me, a general health app that has been shown to improve influenza vaccination rates and address the needs of breast cancer survivors [17][18][19]. Healthy.me Gout was developed after interviews with patients regarding their current gout management [20], a review of commercially available apps for patient selfmanagement of gout [15], and subsequent feedback from gout patients of these apps and the generic version of Healthy.me [21]. Healthy.me Gout contained six features depicted in Figure 4 and summarised in Table 1.…”
Section: Study 2: Pilot Testing Of the Gout Self-management Mobile Apmentioning
confidence: 99%
“…14,21 Some clinicians placed a high priority on the role of food and alcohol intake in gout management, and saw it as an important barrier to optimal gout care, thus potentially perpetuating the stigma and unwittingly creating an environment where reticence about seeking help for gout management could occur. 21 A recent study also found that gout educational resources similarly over-emphasised diet and alcohol as recommended lifestyle changes to help prevent attacks, rather than improving patients' knowledge around the efficacy and mechanisms of ULT or being aware of target serum urate levels. 22 Newer, more appropriate gout resources developed in response to this emphasise that even sustained lifestyle and dietary changes can reduce serum uric acid only by 10%.…”
Section: Original Scientific Paper Original Researchmentioning
confidence: 99%
“…22 Medication non-adherence is substantial in patients with gout, with studies consistently reporting that less than half of patients are adherent with treatment. [23][24][25][26] Recent research suggests that non-adherence may be worse in gout than in any other chronic disease. 27 Many reasons for non-adherence have been identified including limited knowledge about the causes and consequences of gout, lack of understanding about the different therapeutic approaches, uncertainty about therapeutic options to take if an attack occurs, insufficient appreciation of the importance of adherence to ULT, confusion regarding contributions of diet and lifestyle to gout and stigma associated with the diagnosis.…”
mentioning
confidence: 99%
“…27 Many reasons for non-adherence have been identified including limited knowledge about the causes and consequences of gout, lack of understanding about the different therapeutic approaches, uncertainty about therapeutic options to take if an attack occurs, insufficient appreciation of the importance of adherence to ULT, confusion regarding contributions of diet and lifestyle to gout and stigma associated with the diagnosis. 23 25 26 28 In many patients with recurrent gout attacks, the adherence standard required is demanding, as ULT needs to be taken every day to avoid a recurrence. An important factor that impinges on adherence during the early months of therapy is a paradoxical increase in the risk of acute attacks even though serum urate concentrations are falling.…”
mentioning
confidence: 99%
See 1 more Smart Citation